Survivorship of Hemiarthroplasty With Concentric Glenoid Reaming for Glenohumeral Arthritis in Young, Active Patients With a Biconcave Glenoid. Issue 10 (October 2017) - Getz, Charles L.; Kearns, Kenneth A.; Padegimas, Eric M.; Johnston, Peter S.; Lazarus, Mark D.; Williams, Gerald R.
Abstract : Introduction: Hemiarthroplasty with concentric glenoid reaming (known as "ream and run") may be an option for treating glenohumeral arthritis in younger patients with a biconcave glenoid. The goal of this study was to evaluate early results of this technique. Methods: Two senior, fellowship-trained shoulder surgeons (G.R.W. and M.D.L.) performed a retrospective review of 23 patients (24 shoulders) with a biconcave glenoid and end-stage degenerative glenohumeral arthritis treated with hemiarthroplasty with concentric glenoid reaming. The mean patient age at the time of surgery was 50 years. We evaluated the Penn Shoulder Score (PSS), Single Assessment Numeric Evaluation (SANE) score, and Simple Shoulder Test (SST) score or the time to revision surgery. Results: Twenty-four humeral hemiarthroplasties with concentric glenoid reaming were performed in 23 patients. Twenty patients (21 shoulders) reached the end point of 2-year follow-up or revision surgery. Six shoulders (25%) required revision surgery at an average of 2.7 years (range, 0.7 to 7.2 years), and three were lost to follow-up. The remaining 14 patients (15 shoulders) were followed up for an average of 3.7 years (range, 2.3 to 4.9 years). At 2-year follow-up, these 15 shoulders did not require revision surgery and had an average SANE score, PSS, and SST score of 74.5%, 82.9, and 10.4, respectively. Increasing age correlated positively with the SANE score ( r = 0.62; P = 0.015), PSS ( r = 0.52; P = 0.047), and SST score ( r = 0.63; P = 0.012). Early postoperative forward elevation correlated weakly with the PSS ( r = 0.24; P = 0.395), and early postoperative external rotation correlated moderately with the PSS ( r = 0.53; P = 0.044). Final external rotation correlated moderately with the PSS ( r = 0.69; P = 0.005). Discussion: Modest results were achieved with a hemiarthroplasty and concentric glenoid reaming in young patients with end-stage glenohumeral arthritis and a biconcave glenoid. Younger age and stiffness were associated with worse outcomes. Given the high revision rate and the percentage of patients who had unsatisfactory results, this procedure should be performed only after careful patient selection. Patients who are willing and able to undergo aggressive physical therapy focused on achieving early range of motion are more likely to have a satisfactory outcome after humeral hemiarthroplasty with concentric glenoid reaming.